Identification of efferocytosis-related subtypes in gliomas and elucidating their characteristics and clinical significance - Gao, Mengge; Huang, Jinsheng; Yang, Bo; Liu, Qiong; Luo, Miaoqing; Yang, Biying; Li, Xujia; Liu, Xiaofang (Frontiers in Cell and Developmental Biology, 2023)
Gliomas, the most prevalent tumors of the central nervous system, are known for their aggressive nature and poor prognosis. The heterogeneity among gliomas leads to varying responses to the same treatments, even among similar glioma types. With the advancement of treatment approaches, developing new biomarkers and identifying novel subtypes for guiding personalized therapy in glioma patients has become an imperative task. In our research, we identified efferocytosis-related subtypes in gliomas through bulk RNA-seq data analysis, which was further supported by single-cell transcriptomic data, revealing their association with efferocytosis. We then characterized the efferocytosis-related subtypes in terms of immune landscape, intercellular communication, substance metabolism, and genomic features, exploring their relationship with efferocytosis. Moreover, we found that the efferocytosis-related classification is a prognostic factor with robust predictive performance, and is linked to the efficacy of radiotherapy, chemotherapy, and immunotherapy in glioma patients, indicating the role of efferocytosis-related score in guiding treatment for patients.